SPREDs (Sprouty Related Proteins with EVH1 Domain) promote self‐renewal and inhibit mesodermal differentiation in murine embryonic stem cells. Issue 4 (13th March 2015) - Mühl, Bastian; Hägele, Jasmin; Tasdogan, Alpaslan; Loula, Paraskevi; Schuh, Kai; Bundschu, Karin
Abstract : Background : Pluripotency, self‐renewal, and differentiation are special features of embryonic stem (ES) cells, thereby providing valuable perspectives in regenerative medicine. Developmental processes require a fine‐tuned organization, mainly regulated by the well‐known JAK/STAT, PI3K/AKT, and ERK/MAPK pathways. SPREDs (Sprouty related proteins with EVH1 domain) were discovered as inhibitors of the ERK/MAPK signaling pathway, whereas nothing was known about their functions in ES cells and during early differentiation, so far.Results: We generated SPRED1 and SPRED2 overexpressing and SPRED2 knockout murine ES cells to analyze the functions of SPRED proteins in ES cells and during early differentiation. Overexpression of SPREDs increases significantly the self‐renewal and clonogenicity of murine ES cells, whereas lack of SPRED2 reduces proliferation and increases apoptosis. During early differentiation in embryoid bodies, SPREDs promote the pluripotent state and inhibit differentiation whereby mesodermal differentiation into cardiomyocytes is considerably delayed and inhibited. LIF‐ and growth factor‐stimulation revealed that SPREDs inhibit ERK/MAPK activation in murine ES cells. However, no effects were detectable on LIF‐induced activation of the JAK/STAT3, or PI3K/AKT signaling pathway by SPRED proteins.Conclusions: We show that SPREDs promote self‐renewal and inhibit mesodermal differentiation of murine ES cells by selective suppression of the ERK/MAPK signaling pathway in pluripotent cells. Developmental Dynamics 244:591–606, 2015 . © 2015 Wiley Periodicals, Inc. Key Findings: SPREDs support self‐renewal and clonogenicity of murine ES cells. During early differentiation, SPREDs inhibit and delay mesodermal differentiation of murine ES cells into cardiomyocytes. Loss of SPRED2 promotes mesodermal differentiation into cardiomyocytes. SPREDs inhibit LIF‐ and growth‐factor‐induced ERK signaling in murine ES cells.